Finding Balance: Integrating Modern and Salaf Educational Models to Build Character and Efficiency - Istianatul Imamah; Luluk Rosyidatul Umah; Ainur Rofiq (Universitas Nurul Jadid, 2024)
This study aims to analyze how modern education models and salaf can be harmoniously integrated to shape students' character and improve the managerial efficiency of educational institutions. In this study, a qualitative method was used with a case study approach in an educational institution that applied the elements of the two models. Data collection was carried out through in-depth interviews, field observations, and document analysis to explore how hierarchical organizational structures can be applied effectively, how teacher exemplary influences the formation of student character, and how the community supports teacher welfare. The results show that the hierarchical organizational structure provides clarity of roles and responsibilities that improve operational efficiency. On the other hand, teachers' exemplary behavior has proven to be very influential in building students' moral values through direct interaction and consistency in daily behavior. In addition, the active involvement of the community in supporting teachers' welfare not only strengthens social relationships but also creates a more conducive environment for teaching. This study also found that the integration of elements of these two educational models requires adaptive leadership that is able to balance efficiency and character building. The implications of this study are the need for a more flexible approach in the organizational structure of educational institutions, more intensive training strategies to enhance the role of teacher role models, and sustainable community-based programs to support teacher welfare. With the right integration, educational institutions can create a system that is not only managerially efficient but also able to build a generation that has high academic competence and strong character.